Compositional Dependence of Curie Temperature and Magnetic Entropy Change in the Amorphous Tb–Co Ribbons - Wang, Xin (Materials (Basel), 2021)
The Curie temperature (T(c)) and magnetic entropy change (−ΔS(m)), and their relationship to the alloy composition of Tb–Co metallic glasses, were studied systematically in this paper. It was found that, in contrast to the situation in amorphous Gd–Co ribbons, the dependence of Tc on Tb content and the maximum −ΔS(m) vs. T(c) -2/3 plots in Tb–Co binary amorphous alloys do not follow a linear relationship, both of which are supposed to be closely related to the non-linear compositional dependence of Tb–Co interaction due to the existence of orbital momentum in Tb.